Mathematicians in pre-war national defense forces of Lithuania - Ažubalis, Algirdas (Lietuvos matematikos rinkinys, 2002)
The article presents condensed biographical data and activity analysis on the 15 Lithuanian mathematicians who served in pre-war National Defense Forces of Lithuania, with the special emphasis on their contribution to strengthening national defense potential of the country.